PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3) DAN KOMPENSASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN PRODUKSI PADA PT PEPUTRA MASTERINDO KECAMATAN TAPUNG KABUPATEN KAMPAR - Mubarok, Muhammad Fadhil; Andini, Frini Karina (Jurnal Daya Saing, 2025)
Abstract: This research was conducted at PT Peputra Masterindo. The purpose of this study is to determine the effect of occupational safety and health (K3) and compensation on employee work productivity. occupational safety and health and compensation (K3) as an Independent Variable (X) while employee work productivity as a Dependent Variable (Y). The problem in this study is that the work productivity of employees has decreased. The sample of this study was taken as many as 91 respondents from 118 populations calculated using the Slovin formula. The data obtained from the results of the questionnaire were distributed using a simple random sampling technique and then processed for statistical testing through SPSS 30. From the results of the tests carried out, it was shown that occupational safety and health (K3) had a positive and significant effect on employee work productivity, where the calculation was 10.503 > 1.662 and sig <.0.001 < 0.05, then compensation had a positive and significant effect on employee work productivity, where tcount = 2,298 > ttable 1,662 and sig 0.025 < 0.05, as well as occupational safety and health (K3) and compensation for employee work productivity, where the value of fcal was 101. 578 > ftable 3.10 and significant <0.001 < 0.05. Keywords: Occupational Safety and Health (K3), Compensation, Employee Productivity Stainability